Evaluation of optical parameters of quasi-parallel plates with single-frame interferogram analysis methods - Sunderland, Zofia; Patorski, Krzysztof; Pokorski, Krzysztof (Photonics Letters of Poland, 2012)
The surface flatness of transparent plates is frequently tested in Fizeau and Twyman-Green interferometers. In case of quasi-parallel plates, however, a common problem is the additional reflection from the plate rear surface and three-beam interference is encountered. Our new method of deriving shape and optical thickness variations of the plate requires recording two interferograms: a two-beam interferogram without a reference beam and the three-beam interference one. The images are processed using single-frame techniques only. The proposed method does not require modification of a sample or sophisticated equipment and complicated data analysis. Full Text: PDF References: P. de Groot, "Measurement of Transparent Plates with Wavelength-Tuned Phase-Shifting Interferometry", Appl. Opt. 39(16) (2000).CrossRef J. Schwider, Progress in Optics, E. Wolf ed., 28, North Holland, Amsterdam (1990). K. Hibino, B.F. Oreb, P.S. Fairman, and J. Burke, "Simultaneous Measurement of Surface Shape and Variation in Optical Thickness of a Transparent Parallel Plate in Wavelength-Scanning Fizeau Interferometer", Appl. Opt. 43(6), (2004).CrossRef K.G. Larkin, D.J. Bone, and M.A. Oldfield, "Natural demodulation of two-dimensional fringe patterns. I. General background of the spiral phase quadrature transform", J. Opt. Soc. Am. A, 18(8) (2001).CrossRef M.A. Gdeisat, D.R. Burton, M.J. Lalor, "Spatial carrier fringe pattern demodulation by use of a two-dimensional continuous wavelet transform", Appl. Opt. 45 (34) (2006).CrossRef C. Ai, J.C. Wyant, "Effect of spurious reflection on phase shift interferometry", Appl. Opt. 27(14) (1988).CrossRef A. Styk, K. Patorski, "Fizeau interferometer for quasi parallel optical plate testing", Proc. SPIE 7063, 70630P (2008).CrossRef Z. Wang, H. Ma, "Advanced continuous wavelet transform algorithm for digital interferogram analysis and processing", Opt. Eng. 45(4), 045601, (2006).CrossRef